The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1098/rsta.2016.0096
|View full text |Cite
|
Sign up to set email alerts
|

Introduction Wind farms in complex terrains: an introduction

Abstract: Wind energy is one of the fastest growing sources of sustainable energy production. As more wind turbines are coming into operation, the best locations are already becoming occupied by turbines, and wind-farm developers have to look for new and still available areas—locations that may not be ideal such as complex terrain landscapes. In these locations, turbulence and wind shear are higher, and in general wind conditions are harder to predict. Also, the modelling of the wakes behind the turbines is more complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…More than 70% of the Earth's land surface is in complex terrain (Strobach 1991), and thus mountain meteorology has attracted the attention of a wide range of constituencies, including climatologists (Gobiet et al 2014), fluid dynamists (Fernando 2010), and wind engineers (Alfredsson and Segalini 2017). Most past research has been on mesoscales (~1-100 km), spurred by air pollution, aviation, warfare, and energy applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More than 70% of the Earth's land surface is in complex terrain (Strobach 1991), and thus mountain meteorology has attracted the attention of a wide range of constituencies, including climatologists (Gobiet et al 2014), fluid dynamists (Fernando 2010), and wind engineers (Alfredsson and Segalini 2017). Most past research has been on mesoscales (~1-100 km), spurred by air pollution, aviation, warfare, and energy applications.…”
mentioning
confidence: 99%
“…wind farms, especially in Europe, because complex terrain areas are readily found away from human settlements and available flat terrain suitable for wind energy production is at a premium (Alfredsson and Segalini 2017). Complex terrain offers the advantages of wind amplification at ridges, flow jetting through canyons, and remoteness from urban communities with strict noise regulations.…”
mentioning
confidence: 99%
“…The main objective of this research is to perform a comprehensive CFD analysis in hilly terrain to optimize the siting of the turbines by considering their obstruction effect. While several studies have shown that complex terrain affects the wake flow of wind turbines [3][4][5], few research papers have focused on studying its effect on the velocity profile approaching the leading edge of the turbine, which may be an area for further research. Additionally, this work was carried out to assess the efficiency of the CFD model on the airflow distribution in the neutral atmospheric boundary layer (ABL) to describe the impact of topography in the micro-scale wind farms in open hilly terrain, which was considered by the implementation of four wind turbines aligned with two different hill slopes.…”
Section: Introductionmentioning
confidence: 99%
“…Although a lot of emphasis has been on understanding wakes in flat terrain over the past decade (Medici and Alfredsson, 2006;Jimenez et al, 2007;Chamorro and Porté-Agel, 2009;Iungo et al, 2013;Calaf et al, 2010;Porté-Agel et al, 2011;Abkar et al, 2016;Allaerts and Meyers, 2015;Iungo, 2016), complex terrains now finally get the attention they deserve. This is partly due to a prospective shift in development of wind farms from flat to complex terrains caused by saturation of ideal flat terrains and increasing development of wind energy over the past 2 decades (Alfredsson and Segalini, 2017;Feng et al, 2017); it is also partly due to the recent observational and numerical developments. Understanding wakes from turbines in complex terrains, therefore, becomes important for understanding the interaction between terrain and wakes, as well as for better resource assessment and wind farm siting.…”
Section: Introductionmentioning
confidence: 99%